2012
DOI: 10.1111/j.1468-0459.2012.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gridded precipitation for norway using glacier mass‐balance measurements

Abstract: The service seNorge (http://senorge.no) provides gridded temperature and precipitation for mainland Norway. The products are provided as interpolated station measurements on a 1 × 1 km grid. Precipitation gauges are predominantly located at lower elevations such as coastal areas and valleys. Therefore, there are large uncertainties in extrapolating precipitation data to higher altitudes, both due to sparsity of observations as well as the large spatial variability of precipitation in mountainous regions. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…The daily gridded temperature and precipitation were input data for the GSM module, which calculates both snow accumulation and meltwater runoff. A temperature-index approach (Hock, 2003;Engelhardt et al, 2012Engelhardt et al, , 2017 was used in the study for the calculation of melt in the conceptual GSM module. In the GSM module simulation, the precipitation shifts from rain to snow linearly within a temperature interval of T (Table 1).…”
Section: Glacier Melt and Snowmelt Module (Gsm)mentioning
confidence: 99%
“…The daily gridded temperature and precipitation were input data for the GSM module, which calculates both snow accumulation and meltwater runoff. A temperature-index approach (Hock, 2003;Engelhardt et al, 2012Engelhardt et al, , 2017 was used in the study for the calculation of melt in the conceptual GSM module. In the GSM module simulation, the precipitation shifts from rain to snow linearly within a temperature interval of T (Table 1).…”
Section: Glacier Melt and Snowmelt Module (Gsm)mentioning
confidence: 99%
“…The data are based on station measurements which are interpolated on a 1 km horizontal grid for all of mainland Norway on a daily basis from 1957 to the present (Mohr, 2008). Despite some weaknesses with the inter-and extrapolation of precipitation in mountainous regions, different evaluation studies (Mohr, 2009;Dyrrdal, 2010;Engelhardt et al, 2012;Saloranta, 2012) found the gridded data of seNorge to be suitable for mass-balance modelling especially due to its high spatial resolution. …”
Section: Study Sites and Input Datamentioning
confidence: 99%
“…Braun et al, 1994). Since the gridded precipitation data from seNorge for the glacier parts of all catchments (P g ) had already been evaluated in the study by Engelhardt et al (2012), we now used the calculated precipitation correction factors (F g ) from that study for the glacierised areas and calculated the correction factors for the precipitation (P ng ) of the non-glacierised parts (F ng ) of the catchments. The water balance equation for the glacierised and non-glacierised areas was then modified to…”
Section: Precipitation Correctionmentioning
confidence: 99%
“…We used well-established data sets of catchments in Austria (Parajka and Blöschl, 2008;Merz et al, 2011;Haslinger et al, 2014) and Norway (Mohr and Tveito, 2008;Engelhadt et al, 2012;Fleig et al, 2013) that were thoroughly quality-checked and used in other scientific studies. However, measurement errors, uncertainties in the estimation of gridded data from station data, and issues of representativity can still occur, especially in mountainous catchments.…”
Section: Hypothesis 1: For Each Region the Occurrence And Severity Omentioning
confidence: 99%